WORKFORCE DIVERSITY AND ITS IMPACT ON EMPLOYEES PERFORMANCE IN COMMERCIAL BANKS IN NEPAL - Padam Dongol (Galaxy International Interdisciplinary Research Journal, 2022)
Workforce diversity means the heterogeneous composition of employees of an organisation in terms of age, gender, language, ethnic origin, education, marital status, etc. Managing such diversity is essential to add value to an organisation. If workforce diversity is handled correctly, it will give positive benefits. If not addressed correctly, it could lead to negative results. This study aims to analyse the impact of workforce diversity on employees’ performance in Nepalese commercial banks. This study used a self-administered question to collect the different views regarding the workforce diversity of employees from a bank. Out of 27 commercial banks are operating, and 20 are taken as sample banks. Altogether 125 questionnaires were distributed among the employees and returned 99 questionnaires, which indicates a 79.2% sample size of respondents for the study. The empirical relationship of gender, age, education, and ethnicity was computed using the Software Package for Social Science (SPSS). The finding results of the study concluded that all the four workforce diversity variables are positively associated with the performance of the employees in a commercial bank. Thus, the bank has to manage workforce diversity to enhance the performance of the employees.